Changes in serum lipid profile in postmenopausal women with reference to Body mass index (BMI) - Tiwari, Jyoti; Kiran Naagar, Jagrati (International Journal of Medical Research and Review, 2015)
Background and Objective: Menopause is a natural process in the ageing of a women & it denotes the end of reproductive capacity which menifests as cessation of cyclic ovarian function and cyclic menstruation. The various hormonal changes associated with menopause on the serum lipids play an important role in most cardiac problems in this period. As Life expectancy is increasing in terms of age in women and menopause remains relatively unchanged, now women are spending more of their life span in the post-menopausal period.The aim of our study was to evaluate risk factors for coronary artery disease in post menopausal women. This includes study and comparison of the serum lipid profile in premenopausal and postmenopausal women with reference to body mass index. Material and Method: The study was conducted with 100 premenopausal and 100 post menopausal women. The BMI of 50 women in either group was 18.9-24.9 and another 50 women was 25-29.9. Various factors which may alter lipid profile were excluded. After overnight fast of 12 hrs, 5 ml venous blood was withdrawn and sent for lipid profile analysis. Results: We observed that there is significantly high serum levels of total cholesterol,LDL,VLDL and triglycerides and significantly low levels of serum HDL in postmenopausal women group in comparison to their pre menopausal counterparts irrespective of their BMI levels (p=<0.05). Conclusions: Changes in lipid profile in post menopausal women increases the risk of cardio vascular diseases.